Hexamethylmelamine is a potent inducer of deletions in male germ cells of Drosophila melanogaster. - Aguirrezabalaga, I.; Nivard, M.J.; Comendador, M.A.; Vogel, E.W. (Carcinogenesis, 1995)
Chemotherapy-related second tumors constitute a matter of concern in cancer treatment. Therefore, it is of great interest to elucidate the mechanisms by which cytostatic drugs exert their mutagenic and/or carcinogenic activity besides the anticancer effect and the possible relationship among them. A useful and informative approach to this problem is the analysis of the mutation spectra induced by these drugs in eukaryotic organisms. Sequence analysis of the mutations induced by hexamethylmelamine, a crosslinking agent extensively used in the treatment of ovarian cancer, in male germ cells of Drosophila was conducted using the v locus as reporter gene. Both intra-locus and multi-locus deletions were induced whereas based changes were almost absent. Thus, it is proposed that deletions are likely to be involved in the generation of second malignancies in hexamethylmelamine-treated patients. It has to be stressed that systems, such as v, capable of efficiently recovering mutations caused by big losses of DNA, should be used for the study of mutational spectra induced by cross-linking agents.